Educational Leadership Strategies In Supporting Technology Adaptation In Japanese Private Schools - Yuko Takhahasi; Sofia Rossi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This study aims to explore educational leadership strategies in supporting technology adaptation within Japanese private schools, emphasizing how school leaders drive the integration of technology into the learning process. Utilizing a qualitative research approach, data were collected through interviews, observations, and document analysis involving school leaders, teachers, and other stakeholders. The study reveals that effective educational leadership strategies include setting a clear vision for technology’s role in education, providing ongoing professional development for teachers, and allocating resources to foster a conducive learning environment. Challenges, such as resistance to change among teachers, technical issues, and balancing innovation with curriculum requirements, were also identified. Findings highlight the importance of collaboration among teachers, students, and stakeholders to overcome barriers to technology implementation. Practical implications include the need for continuous professional development, effective communication channels, and a culture of innovation that encourages creative approaches to technology integration. These strategies not only facilitate technology adaptation but also create a more interactive, relevant, and enriched learning experience that supports long-term educational success.